MENYIBAK MISTERI ALAM RAYA MELALUI AYAT-AYAT SEMESTA - Nurul Wakia; Sabriadi HR (HISABUNA: Jurnal Ilmu Falak, 2021)
Abstract This paper reveals the secrets of the universe through the verses of the universe. The data is obtained through library research. The results show that the planet Earth and humans have the ability to vary the order of the universe. In the universe, humans see the existence of various organizations of matter in the form of various luminous objects such as moons, planets, stars, nebulae, star clusters, galaxies, and galaxy clusters.This magnificent material figure of the universe, whether it is successful or not successfully captured by the human senses, is controlled by "supernatural powers" which are called the force. Through the character of style, the human mind explores its wanderings in the world of science and uses that knowledge to create works of technology and art. Muslims acquire this knowledge through the Quran.The arrival of Allah’s revelation to mankind is a methodology for developing knowledge about human life and the universe. An "existence of truth" that cannot be achieved only by scientific methodology. Al Quran is an "existence of truth" that is conveyed to humans in a reliable, communicative, and preserved way.Knowing the existence of the truth of the Quran can only be achieved through a system of faith. The existence of the universe is positioned to awaken various human intelligences, including spiritual intelligence which is guided by the verses of the Quran so that it leads to the level of human faith, a measure of the level of human closeness to the Creator. Keywords: reveal, mystery of nature, universe verses Abstrak Tulisan ini mengungkap rahasia alam raya melalui ayat-ayat sesmesta. Data diperoleh melalui penelitian kepustakaan (library research. Hasil penelitian menunjukkan planit bumi, manusia, memiliki kemampuan dengan berbagai keteraturan alam semesta. Di alam semesta manusia melihat eksistensi keragaman organisasi materi dalam bentuk berbagai benda yang bercahaya seperti bulan, planit, bintang, nebula, gugus bintang, galaksi, dan gugus galaksi. Sosok materi alam semesta yang megah ini baik yang berhasi latau belum/tidak berhasil diindera manusia dikendalikan oleh “tangan-tangan ghaib” yang disebut dengan gaya. Melalui karakter gaya itu akal manusia menjelajah pengembaraannya dalam dunia ilmu pengetahuan dan menggunakan pengetahuan itu untuk membuat karya teknologi dan seni. Umat Islam memperoleh pengetahuan itu melalui al Qur’an. Sampainya wahyu Allah ini kepada umat manusia merupakan sebuah metodologi untuk mengembangkan ilmu pengetahuan tentang kehidupan manusia dan alam semesta. Suatu “eksistensi kebenaran” yang tak dapat dicapai hanya dengan metodologi sains. Al Qur’an merupakan suatu “eksistensi kebenaran” yang disampaikan kepada manusia melalui cara terpercaya, komunikatif, dan terjaga. Mengenal eksistensi kebenaran al Qur’an hanya dapat dicapai melalui system keimanan. Keberadaan alam semesta diposisikan untuk membangkitkan berbagai kecerdasan manusia, diantaranya adalah kecerdasan spiritual yang dituntun oleh ayat-ayat al Qur’an sehingga berujung pada tingkat keimanaan manusia, sebuah ukuran tingkatan kedekatan manusia kepada sang Pencipta. Kata Kunci: Menyibak, misteri alam, ayat-ayat semesta